Analisis Hukum Atas Penerapan Hukuman Mati Terhadap Tindak Pidana Korupsi di Indonesia Dihubungkan dengan Undang Nomor 39 Tahun 1999 Tentang Hak Asasi Manusia - Abellio Jhose Sitompul (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study is motivated by the ongoing debate regarding the application of the death penalty to perpetrators of corruption in Indonesia, particularly in relation to the protection of human rights as stipulated in Law Number 39 of 1999. The purpose of this research is to explain the extent to which the death penalty can be appropriately and proportionally applied to corruptors while considering human rights principles. This study employs a normative legal approach focused on the analysis of statutory regulations and relevant legal literature. The data is analyzed using a qualitative juridical method, emphasizing a normative review of applicable positive law. The findings reveal a discrepancy between the imposition of the death penalty for corruption crimes and the right to life guaranteed by Indonesia’s human rights legal instruments. The implication of this research highlights the need to reconsider the policy of capital punishment for corrupt practices to ensure alignment with the principles of justice, humanity, and respect for human rights within the national legal system.